Carbon footprint heterogeneity across elderly groups in China - Yunyue Wang; Yafei Wang (Environmental Research Communications)
Assessing the elderly’s environmental impact is crucial as aging deepens. This paper incorporates age heterogeneity and urban-rural heterogeneity within the elderly into the study of aging’s impact on the environment, dividing the elderly population into four subgroups. Utilizing an environmentally extended multi-region input-output(EE-MRIO) model and data from 12,000 households, the carbon footprints of four subgroups was calculated. Findings reveal significant urban-rural and age-related heterogeneities in carbon emissions among those aged 60 and above. Urban elderly have higher per capita carbon footprints than rural elderly, and ‘the younger elderly’ have higher footprints than ‘the oldest old’. This heterogeneity extends to carbon footprint’s distribution: Urban elderly lean towards enjoyable consumption, while rural elderly prioritize survival. ‘The younger elderly’ have a greater carbon footprint from transport. This paper nests Chinese and global EE-MRIO, showing that global economies are more impacted by China’s elderly demand than mainland China itself. Furthermore, urban-rural structure has a greater impact on global carbon emissions compared to age structures.